AB0496 Corticosteroid Use across 52 Weeks of Belimumab Therapy in SLE Patients with High Disease Activity: Combined Analyses from the BLISS Trials. (10th June 2014) - Van Vollenhoven, R.; Petri, M.; Wallace, D.J.; Roth, D.; Molta, C.; Hammer, A.; Tang, T.; Thompson, A.
Abstract : Background: Patients with systemic lupus erythematosus (SLE) frequently receive corticosteroids (CS) as part of standard therapy. Objectives: We examined the effects of belimumab on cumulative CS dose across 52 weeks in patients with high disease activity from two randomised, controlled trials. Methods: Data from BLISS-52 (NCT00424476 ) and BLISS-76 (NCT00410384 ) were pooled (GSK200317). Patients with high disease activity (defined as anti-dsDNA positive and low complement) treated with CS at baseline and randomised to receive belimumab 10 mg/kg plus standard therapy or placebo plus standard therapy were compared. A steroid taper was allowed in each study. The primary endpoint was the cumulative change from baseline (average dose over the prior 7 days) in CS dose (prednisone equivalent) through Week 52. Rank analysis of covariance was applied. Cumulative dose reductions and increases, and change from baseline in average daily CS dose were examined. Results: At baseline, 538 (91%) subjects with high disease activity (N=592) received CS therapy: 275 received belimumab 10 mg/kg and 262 received placebo. Most subjects were female (n=507, 94.2%); mean age was 34.3 (10.5 SD) years, 66.4% of subjects had a SELENA-SLEDAI score ≥10 and mean CS dose (prednisone equivalent) was 12.8 (8.3 SD) mg/day. Baseline parameters for subjects treated with CS were similar between treatment groups. The mean cumulative change from baseline in CS dose was 1015 mg belimumab 10 mg/kg compared with 1560 mg placebo (p<0.01). The mean of all cumulative decreases in CS dose was -755 mg belimumab 10 mg/kg and -555 mg placebo (p<0.05). The mean of all cumulative increases in CS dose was +1770 mg belimumab 10 mg/kg and +2115 mg placebo (p<0.05). The mean change from baseline in average daily CS dose was 2.8 mg belimumab 10 mg/kg and 4.3 mg placebo (p<0.01). Conclusions: Patients with SLE with high disease activity have a substantial CS burden. Although there was an increase in total CS dose in both treatment groups over 52 weeks, this increase was significantly smaller in patients who received belimumab 10 mg/kg plus standard therapy compared with standard therapy alone. Disclosure of Interest: R. Van Vollenhoven Grant/research support: AbbVie, BMS, GlaxoSmithKline, Pfizer, Roche and UCB, Consultant for: Abbvie, Biotest, BMS, GlaxoSmithKline, Lilly, Merck, Pfizer, Roche, UCB, Vertex and Janssen, M. Petri Grant/research support: GlaxoSmithKline, D. Wallace Consultant for: GlaxoSmithKline, D. Roth Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, C. Molta Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, A. Hammer Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, T. Tang Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, A. Thompson Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline DOI: 10.1136/annrheumdis-2014-eular.4969